Penerapan Graf Kompatible Pada Durasi Lampu Lalu Lintas di Simpang Empat Andalas Kota Padang - Monalisa; Algusduri, Nopra; Castama, Fadly Braja (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Traffic congestion is a serious issue in densely populated urban areas, affecting mobility and transportation efficiency. Congestion often occurs due to the lack of synchronization between traffic signal timings and a high volume of vehicles. In an effort to address this problem, we applied a compatible graph approach to manage the traffic signal durations at the Andalas Four-Way Intersection. This study utilized traffic data obtained through field observations. Subsequently, we employed compatible graph analysis to model the traffic network and applied the Webster method to calculate traffic signal durations. Compatible traffic flows are two traffic streams that, when operating simultaneously, do not lead to accidents. The research findings showed that the waiting time at the Andalas Four-Way Intersection was 578 seconds, while with the compatible graph approach, it reduced to 114 seconds. The calculation of traffic signal waiting times using the compatible graph approach is more optimal compared to the existing configuration. Keywords ;; ; ; . Abstrak Kemacetan lalu lintas menjadi masalah serius di perkotaan yang padat penduduk sehingga memengaruhi mobilitas dan efisiensi transportasi. Kemacetan sering terjadi karena kurangnya sinkronisasi waktu tunggu lampu lalu lintas dan volume kendaraan yang tinggi. Dalam upaya mengatasi masalah ini, kami menerapkan graf kompatible dalam mengelola durasi lampu lalu lintas di Simpang Empat Andalas. Penelitian ini menggunakan data lalu lintas yang diperoleh melalui pengamatan lapangan. Kemudian, kami menggunakan analisis graf kompatible untuk memodelkan jaringan lalu lintas dan menerapkan metode Webster untuk menghitung durasi lampu lalu lintas. Arus yang kompatible merupakan dua buah arus lalu lintas jika keduanya berjalan bersamaan tidak menimbulkan kecelakaan. Hasil penelitian ini diperoleh waktu tunggu di Simpang Empat Andalas selama 578 detik sedangkan dengan graf kompatible menghasilkan 114 detik. Perhitungan waktu tunggu lampu lalu lintas menggunakan graf kompatible lebih optimal dibandingkan dengan pengaturan yang sudah diterapkan. Kata kunci: graf kompatible; Simpang Empat Andalas; lampu lalu lintas; waktu tunggu; metode webster.